THE EFFECT OF LOCAL TAX REVENUE ON THE INCREASE IN REGIONAL ORIGINAL INCOME OF BELU DISTRICT IN 2012-2022 - Novrianus Kofi (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
In the period of 2012-2022, the Belu Regency Government faces challenges in maximizing Regional Original Income (PAD) to finance development and public services. The purpose of this study is to determine how much the Influence of Regional Tax Revenue on the Increase in Belu Regency's Regional Original Income in 2012-2022. This study uses a quantitative research method with a regression research type. While the type of data used is secondary data. The results of the study indicate that Regional Tax Revenue has an influence on the Increase in Belu Regency's Regional Original Income in 2012-2022. Interpretation of the results of the t-test and F-test is a study on the Influence of Regional Tax Revenue on the Increase in Belu Regency's Regional Original Income in 2012-2022 produces a significant linear regression equation